The effect of good leadership / Nur Syazwani Bakar, Norli Ezzati Mohd Abu Hassan AlShari and Nurul Syahirah Mdsalleh - Bakar, Nur Syazwani; Mohd Abu Hassan AlShari, Norli Ezzati; Mdsalleh, Nurul Syahirah (2014)
This article is about how a good leader will affect many things in an organization, especially the subordinates as well as customers. Here are some of the effect by a good leadership which are inspirational motivation, intellectual stimulation, build the individualized consideration, a good environment, improve the professional performance, enhanced job satisfaction, the organization will grow, encourage teamwork, and providing high qualities services. A good leader will /eaqf to the successful organization.